Herpetofauna Diversity at Eaglewood Gyrinops vesteegii Conservation Area in Pusuk Protected Forest, Lombok - Yuliadi Zamroni; Ahmad Jupri; Baiq Farista; Aida Muspiah; Tri Mulyaningsih (Jurnal Penelitian Pendidikan IPA, 2023)
Pusuk Protected Forest at Lembah Sari Village, Batu Layar District, western Lombok is Gyrinops vesteegii conservation area, the one of eaglewood trees in the Lesser Sunda Islands. Studying diversity and distribution of herpetofauna in conservation area to understanding how this fauna could be stabilized the community structure of organisms in the ecosystems with their act as secondary and tertiary consumers in food web organization. Herpetofauna in this area was captured by visual encounter surveys (VES) method. Eleven species of herpetofauna have been collected from eaglewood conservation area in protected forest of Pusuk, is comprised by four species of amphibians (Duttaphrynus melanostictus, Ingerophrynus biporcatus, Limnonectes dammarmani and Limnonectes kadarsani) and seven species of reptiles (Ahaetulla prasina, Cyrtodactylus petani, Dendrelaphis pictus, Draco volans, Eutropis multifasciata, Gekko gecko, Sphenomorpus melanopogon and Sibynopis geminatus). This animal group plays as a role in maintaining the stability of eaglewood ecosystems by controlling its pest populations such as moth larvae of Heortia vitessodes and white lice of Dysmicoccus brevipes. Based on this research, higher diversity of herpetofauna with varying types of their habitats could be control the varying types of forest tree pests